(untitled) (Journal of Parents and Teachers, 2026)
This article highlights the cultural and social importance of comics. As a result, comics are used as a teaching tool because of the values they convey, without neglecting their role as entertainment. Furthermore, the article proposes an interdisciplinary classroom activity that addresses linguistic aspects, psychomotor skills, artistic expression, history, and literature.